2018
DOI: 10.1051/0004-6361/201732255
|View full text |Cite
|
Sign up to set email alerts
|

Probing star formation and ISM properties using galaxy disk inclination

Abstract: Disk galaxies at intermediate redshift (z ∼ 0.7) have been found in previous work to display more optically thick behaviour than their local counterparts in the rest-frame B-band surface brightness, suggesting an evolution in dust properties over the past ∼6 Gyr. We compare the measured luminosities of face-on and edge-on star-forming galaxies at different wavelengths (Ultraviolet (UV), midinfrared (MIR), far-infrared (FIR), and radio) for two well-matched samples of disk-dominated galaxies: a local Sloan Digi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 183 publications
3
31
5
Order By: Relevance
“…Both the symbols and lines are color-coded with the gas-phase metallicity shown by the color bar. Leslie et al 2018). Some authors concluded from this that galaxy stellar mass is the most fundamental parameter determining the dust obscuration in SFGs (Garn & Best 2010;Zahid et al 2014b).…”
Section: Irx Does Not Depend On Stellar Massmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the symbols and lines are color-coded with the gas-phase metallicity shown by the color bar. Leslie et al 2018). Some authors concluded from this that galaxy stellar mass is the most fundamental parameter determining the dust obscuration in SFGs (Garn & Best 2010;Zahid et al 2014b).…”
Section: Irx Does Not Depend On Stellar Massmentioning
confidence: 99%
“…The mass-IRX relation has been widely examined over a wide redshift range (Reddy et al 2010;Heinis et al 2014;Whitaker et al 2014;Álvarez-Márquez et al 2016), finding that it evolves little out to z=3 at the low-mass end of M * <10 10.5 M in contrast to a rapid evolution at the high-mass end (Whitaker et al 2014; Leslie et al 2018). Some authors concluded from this that galaxy stellar mass is the most fundamental parameter determining the dust obscuration in SFGs (Garn & Best 2010;Zahid et al 2014b).…”
Section: Irx Does Not Depend On Stellar Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Graham & Worley (2008) and Sargent et al (2010) independently found that the inclination effects of dust can bias measurements of the galaxy B-band surface brightness to be » -0.5 mag arcsec 2 brighter for edge-on galaxies. Measurements of the half light radius have been shown to be increased by up to 110% for edge-on galaxies compared to face-on galaxies (Möllenhoff et al 2006;Leslie et al 2018b). UV magnitudes have been shown to be 1-2 magnitudes fainter for edge-on galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we quantified the consequences of not incorporating variation in γ and assuming radial symmetry when determining inclination. We compared the median, 16th, and 84th percentiles of our sample's inclination PDFs to inclinations and uncertainties of our sample calculated using Equation (1) assuming radial symmetry and the commonly used fixed values of γ = 0.15 and 0.2 (e.g., Maller et al 2009;Sargent et al 2010;Chevallard et al 2013;Wang et al 2018;Leslie et al 2018b) as well as γ = 0.08 assumed by Tuffs et al (2004) in deriving the inclinationdependent attenuation curves. These calculated values for the fixed values of γ are in excellent agreement with the median PDF inclinations for galaxies with i  30°.…”
mentioning
confidence: 99%